Growth performance and survival rate of Asian seabass (Lates calcarifer) with the utilization of vitamin C in feed - Aris, Muhammad; Muchdar, Fatma (e-Journal BUDIDAYA PERAIRAN, 2020)
This study aimed to determine the effect of vitamin C enrichment on fresh trash feed on the growth of Asian seabass (L. calcarifer) and their optimal dosage. The study used a completely randomized design with 4 treatments and 5 replications for each treatment. The treatment given was a dose of vitamin C 3.5 g / kg of fresh trash feed (A); dose of vitamin C 4 g / kg fresh trash feed (B); dose of vitamin C 4.5 g / kg fresh trash feed (C); and fresh trash feed without vitamins (D). Enrichment of vitamin C in fresh trash feed significantly affected the absolute growth of Asian seabass. Treatment A, 17,60; treatment B, 19.79; treatment C, 17.11; and treatment D 13.32 g. Enrichment of vitamin C in fresh trash feed also significantly affected the specific growth of Asian seabass. Treatment A, 2.41%; treatment B, 2.60%; treatment C, 2.37%; and treatment D 2.04%. Enrichment of vitamin C in fresh trash feed did not significantly affect the survival of Asian seabass. Treatment A, 42.5%; treatment B, 47.5%; treatment C, 45%; and 40% D treatment